TRANSITION OF GEOLOGICAL ENTERPRISES TO INTERNATIONAL FINANCIAL REPORTING STANDARDS (Modern education and development, 2024)
This thesis examines the critical necessity for geological enterprises to adopt International Financial Reporting Standards (IFRS) and explores the practical implications of this transition. In the context of a globalized economy, the adoption of IFRS is essential to enhance financial transparency and attract international investment. The paper delves into the challenges faced by geological enterprises, including the complexities of calculating asset depreciation, valuing natural resources, and aligning financial reporting practices with global standards. Moreover, it highlights the positive outcomes of transitioning to IFRS for Uzbekistan’s mining and geology sector, such as improved financial stability and increased foreign investment.